Challenges of Implementing Forest Land Rehabilitation in the Nusantara Capital City (IKN) - Adelia Juli Kardika; Nur Rahma Muzadiyah Dinata; Erna Rositah; Kiamah Fathirizki Agsa Kamarati (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Field assistants for forest and land rehabilitation have an important role in supervising and ensuring that rehabilitation projects run according to the plans and objectives that have been set. In the implementation of forest and land rehabilitation, various challenges are often encountered that can affect project implementation and its final results. The purpose of this study is to determine the challenges faced in implementing forest and land rehabilitation in the capital city of the archipelago. The methods used are observation and interviews. Furthermore, it was analyzed using the miles and huberman model, data presentation in the form of narrative text. The research results obtained were the challenges encountered at forest and land rehabilitation locations in the capital city of the archipelago, including poor infrastructure and accessibility conditions as the main challenges; hilly and steep topography of the area adds to the difficulty of access; lack of operational transportation so that it hampers the process of assistance, distribution of tools, materials and logistics; climate change during extreme weather affects work and the availability of clean water; pest and disease attacks; land conflicts with local communities and overlapping land with the capital city development party; limited number of human resources experienced in the field of forest and land rehabilitation; dust from hauling roads.